Characterization of the efficiency of microbore liquid chromatography columns by van Deemter and kinetic plot analysis. Issue 20 (4th October 2016) - Hetzel, Terence; Loeker, Denise; Teutenberg, Thorsten; Schmidt, Torsten C.
Abstract : The efficiency of miniaturized liquid chromatography columns with inner diameters between 200 and 300 μm has been investigated using a dedicated micro‐liquid chromatography system. Fully porous, core–shell and monolithic commercially available stationary phases were compared applying van Deemter and kinetic plot analysis. The sub‐2 μm fully porous as well as the 2.7 μm core–shell particle packed columns showed superior efficiency and similar values for the minimum reduced plate heights (2.56–2.69) before correction for extra‐column contribution compared to normal‐bore columns. Moreover, the influence of extra‐column contribution was investigated to demonstrate the difference between apparent and intrinsic efficiency by replacing the column by a zero dead volume union to determine the band spreading caused by the system. It was demonstrated that 72% of the intrinsic efficiency could be reached. The results of the kinetic plot analysis indicate the superior performance of the sub‐2 μm fully porous particle packed column for ultra‐fast liquid chromatography.